Analis Lingkungan Kerja, Kompensasi, dan Employee Engagement Terhadap Kinerja Karyawan Surya Toserba Ciledug Kab.Cirebon - Ririn Marshelina; Azizah Indriyani; Muhammad Syaifulloh (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to analyze the influence of the work environment, compensation and employee engagement on the performance of employees at Surya Toserba Ciledug, Cirebon Regency. The sampling technique in this research used non-probability sampling, namely purposive sampling with a saturated sample method for 54 employees. The data analysis techniques used were validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination (R2) tests, t tests, and F tests assisted by using SPSS 25 analysis tools. The results of this research from partial tests show that the work environment influences employee performance from the results obtained, namely 3,569 > 2,008, and the sig value on employee performance is 0.001 < 0.05. compensation has a positive effect on employee performance at Surya Toserba Ciledug Cirebon, with a value of 2,407 > 2,008, and a sig value on employee performance of 0.020 < 0.05. Employee engagement has a positive and significant effect on employee performance. From the results obtained, namely 3,128 > 2,008, and the sig value on employee performance is 0.003 < 0.05, it can be concluded that employee engagement influences employee performance at Surya Toserba Ciledug Cirebon. The higher the level of employee engagement, the better the performance.